DESCRIPTION OF SUBJECTIVE WELL-BEING IN ONLY DAUGHTERS RELATED TO THE NYENTANA TRADITION IN TABANAN - Krisadelia, Ni Putu; Tobing, David Hizkia (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Nyentana is a marriage system where the woman proposes to the man, and then the man moves into the woman's family. Nyentana marriage is an alternative for families who have only daughters to continue the descent. Finding a man who is willing to commit to nyentana is not easy, especially for the only daughters in the Tabanan district, which is known for its nyentana tradition. The various problems that only daughters face can cause psychological issues. This study aims to describe the subjective well-being of only daughters in relation to the nyentana tradition in Tabanan. This research uses a qualitative method with a phenomenological approach. Data collection was conducted through semi-structured interviews with five respondents who were only daughters aged 21-24 years and domiciled in Tabanan. The data analysis used theoretical coding. The results found five findings that described subjective well-being in only daughters, such as awareness of responsibility, family love, gratitude, and life principles in the nyentana tradition; challenges in getting nyentana; self-assessment as an only child; dreams for the future; and responses to problems. This study is expected to be a reference for individuals who seek to improve their quality of life.